Expression pattern of extracellular matrix proteins in the pancreas of various domestic pig breeds, the Goettingen Minipig and the Wild Boar - Meyer, T; Czub, S; Chodnewska, I; Beutner, U; Hamelmann, W; Klöck, G; Zimmermann, U; Thiede, A; Ulrichs, K (Annals of transplantation, 1997)
In spite of progress in biotechnology, isolation of porcine pancreatic islets remains a difficult task with unpredictable results. One reason could be the lack of knowledge as to the expression of extracellular matrix proteins in porcine exocrine and endocrine tissues, particularly in "islet capsules". Such proteins are subject to digestion by proteases, yet they might have a protective function for the fragile islets. Of our study was a detailed histological analysis of the extracellular matrix proteins in various pig breeds. A broad panel of commercial, human-specific antibodies were used, since antibodies against porcine tissue were not available. Frozen pancreatic tissue section of 7 domestic pig breeds, the Goettingen Minipig and the Wild Boar were stained with antibodies against collagen types I, II, III, IV, V, VI, VII, IX, laminin, fibronectin, vitronectin and elastin. Binding of antibodies was detected by immunoperoxidase and evaluated microscopically. Human and rat tissue was treated in the same way. (1) With the exception of anti-collagen type II, type VII and vitronectin, all antibodies revealed distinct binding patterns in the pancreas of the different pig breeds. However these antibodies bound on human cartilage and skin. (2) Collagen types I, III, IV, laminin and fibronectin are expressed on porcine pancreatic "islet capsules". (3) Expression levels of these proteins on "islet capsules" vary in the different pig breeds. However, no significant differences could be found in the expression pattern of collagen types I, III, IV, laminin and fibronectin, comparing domestic, experimental and wild type pigs. (4) Older individuals (Goettingen Minipig) appear to express higher levels of proteins on "islet capsules" than younger ones. Antibodies with specificity for human extracellular matrix proteins can be used successfully in the porcine pancreas. Thus, analysis of the structure and composition of porcine pancreatic tissue can be performed even without pig-specific antibodies. Particularly, the effects of various proteases and collagenases on the pancreatic tissue can now be monitored by immunohistochemical analysis allowing a rational design of protease mixtures for the isolation of pancreatic islets.